2002
DOI: 10.1902/jop.2002.73.6.597
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Calculus Detection With Fluorescence Induced by 655 nm InGaAsP Diode Laser Radiation

Abstract: The present study indicates that subgingival calculus can be reliably detected on extracted teeth using laser fluorescence induced by the 655 nm diode-laser radiation. In vivo studies are necessary to evaluate the clinical utility of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 12 publications
6
64
1
2
Order By: Relevance
“…The challenge with the VistaCam device in its current optical configuration is that it is not designed for use in the periodontal pocket environment, but if suitable changes were made in this direction, the results from this study show promise for its eventual use for guiding clinicians in the detection of subgingival calculus. The overall approach then would be similar to using laser fluorescence to inform the decision around stopping or continuing subgingival calculus debridement (Folwaczny, Heym, Mehl, & Hickel, 2002; Krause, Braun, & Frentzen, 2003; Folwaczny, Heym, Mehl, & Hickel, 2004; Shakibaie & Walsh, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The challenge with the VistaCam device in its current optical configuration is that it is not designed for use in the periodontal pocket environment, but if suitable changes were made in this direction, the results from this study show promise for its eventual use for guiding clinicians in the detection of subgingival calculus. The overall approach then would be similar to using laser fluorescence to inform the decision around stopping or continuing subgingival calculus debridement (Folwaczny, Heym, Mehl, & Hickel, 2002; Krause, Braun, & Frentzen, 2003; Folwaczny, Heym, Mehl, & Hickel, 2004; Shakibaie & Walsh, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…To assist dental practitioners in detecting deposits of subgingival calculus, a number of novel methods have been developed, including visible red light (655 nm)-induced fluorescence (LF) [5,6]. This approach has been used in three systems from the one manufacturer (Kavo, Biberach, Germany) -the "classic" DIAGNOdent, the DIAGNOdent pen, and the KEY3 laser.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, 655 nm InGaAsP (indium gallium arsenide phosphate) diode laser radiation has been included in an Er:YAG laser device to induce fluorescence in subgingival calculus (Folwaczny et al 2002, Krause et al 2003. Preliminary clinical and histological results have shown that fluorescence-controlled (feedback system) Er:YAG laser radiation enabled an effective removal of subgingival calculus and a predictable root surface preservation in comparison with hand instruments (Schwarz et al 2006, Krause et al 2007).…”
Section: Periodontal Applications Of Diode Lasersmentioning
confidence: 99%